2016
DOI: 10.3126/njn.v12i2.15895
|View full text |Cite
|
Sign up to set email alerts
|

Study of Traumatic Brain Injury Due To Recent Earthquake in Manipal Teaching Hospital

Abstract: The objective of this study was to review the demographics, causes injury, severity, treatment and outcome of traumatic brain injuries in victims of the April 2015 earthquake who were admitted in Manipal Teaching Hospital, Pokhara. A total of 37 patients was admitted under Neurosurgery Services. Collapse of buildings was the commonest cause of head injury. The majority of them had mild head injury. Associated injuries to other parts of the body were present in 40.54% patients.Nepal Journal of Neuroscience 12:6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…All cases of traumatic brain injuries can be operated by a single incision in the bicoronal site because most of the time injury occur in either parietal, temporal or frontal site. But if the case is related to isolated bilateral temporal contusion single incision can't be made as it requires two bilateral incisions [16][17] .…”
Section: Discussionmentioning
confidence: 99%
“…All cases of traumatic brain injuries can be operated by a single incision in the bicoronal site because most of the time injury occur in either parietal, temporal or frontal site. But if the case is related to isolated bilateral temporal contusion single incision can't be made as it requires two bilateral incisions [16][17] .…”
Section: Discussionmentioning
confidence: 99%
“…22,44,45 On the other hand, 2 studies showed that more patients occurred following 48 hours compared with initial 24 hours in Pakistan and Nepal. 42,47…”
Section: Neurological Surgerymentioning
confidence: 99%
“…There are several protocols surgeons use in order to reduce intracranial pressure. Surgery is typically required for trauma injuries such as fractures and bruising [7,8]. Recent years have seen significant improvements in TBI management through both medical and surgical methods.…”
Section: Introductionmentioning
confidence: 99%